Strategy for Integration of Science and Religion in Islamic Education In 4.0 Era - Robiatul Adawiyah (At-Ta'dib, 2021)
"Strategy  for  Integration  of  Science  And  Religion  in  Islamic Education In Era 4.0 (Case Study of Yayasan Darul Qur'an Mulia Putri SMPIT Gunung Sindur –  Bogor)". The  purpose  of  this  research  is  to  find  out  the  integration  of science and religion in Islamic education in the 4.0 era at yayasan Darul Qur'an  Mulia  Putri  SMPIT  Gunung  Sindur  –  Bogor  and  to know  the  integration  strategy  in  it  through  four  indicators, namely curriculum  aspects,  aspects  of  learning  models,  hr  aspects,  and infrastructure aspects. This  research  uses  quantitative-qualitative  methods  based  on literatures aimed at finding strategies for the integration of design and religion in Islamic education in the 4.0 era. Data mining process using Analytic Network Process (ANP) method. The results showed that 1). integration of science and religion in  Islamic  education  in  era  4.0  at  Yayasan  Darul  Qur'an  Mulia  Putri SMPIT Gunung Sindur –  Bogor consists of three integrations, namely:  a.  integration  of  the  Foundation  with  integrated  schools  in which  there  are  three  aspects;  bodiesiyah,  fikriyyah,  and  ruhiyyah,  b. integration  of  curriculum  consisting  of  diknas  curriculum,  pesantren curriculum, tarbiyah curriculum, and Qur'an curriculum, c. integration integration  between  parents  and teachers,  curriculum,  and  educational concepts,  and  2).  integration  strategy  within  the  Foundation  through four indicators, namely curriculum aspects, aspects of learning models, hr aspects, and infrastructure aspects are with seven strategies, namely: a. encouraging the development of integration between the two in the era  of  4.0,  b.  choosing  integration  education  between  the  two,  c. innovation  in  learning  model  development, d. providing education  to HR,  e.  strengthening  technology  and  networks  to  Islamic  educational institutions,  f.  integration  innovation  of  both  through  proj ectly  time  , and g. strengthen human resources competencies